US system of oversight for genetic testing: a report from the Secretary''s Advisory Committee on Genetics, Health and Society. (September 2008) - Aspinall, M; Au, S M; Billings, P; Dreyfuss, R; Evans, J P; Ferreira-Gonzalez, A; FitzGerald, K T; Fomous, C; Licinio, J; Burns McGrath, B; Miller, P S; Telfair, J; et al.
As genetic testing technology is integrated into healthcare, increasingly detailed information about individual and population genetic variation is available to patients and providers. Health professionals use genetic testing to diagnose or assess the risk of disease in individuals, families and populations and to guide healthcare decisions. Consumers are beginning to explore personalized genomic services in an effort to learn more about their risk for common diseases. Scientific and technological advances in genetic testing, as with any newly introduced medical technology, present certain challenges to existing frameworks of oversight. In addition, the growing use of genetic testing will require a significant investment in evidence-based assessments to understand the validity and utility of these tests in clinical and personal decisionmaking. To optimize the use of genetic testing in healthcare, all sectors of the oversight system need to be strengthened and yet remain flexible in order to adapt to advances that will inevitably increase the range of genetic tests and methodologies.